Lobachova І. М. Synonyms of the Ukrainian texts of the holy bible of the XXth century - Lobachova І. М. (Philological Treatises, 2020)
The synonymous pairs of nouns, which were used in the Ukrainian translations of the Bible by I. Ogiyenko and I. Khomenko in correlative contexts are selected and analyzed. The main features of the using of these pairs are found out, the stylistic differentiation of vocabulary is determined.